Food wastes and sewage sludge as feedstock for an urban biorefinery producing biofuels and added‐value bioproducts. Issue 2 (28th May 2019) - Battista, Federico; Frison, Nicola; Pavan, Paolo; Cavinato, Cristina; Gottardo, Marco; Fatone, Francesco; Eusebi, Anna L; Majone, Mauro; Zeppilli, Marco; Valentino, Francesco; Fino, Debora; Tommasi, Tonia; et al.
Abstract: The updated Bioeconomy Strategy document "A sustainable bioeconomy for Europe: strengthening the connection between economy, society and the environment", which was issued by the European Commission in October 2018, encourages the exploitation of organic wastes according to a pyramidal hierarchy in which the extraction of valuable biomolecules, which will be used as they are or as precursors of high‐added‐value compounds, is a priority in biofuel production. This review considers a biorefinery platform in which food waste and sewage sludge are adopted to produce volatile fatty acids (VFAs) through a dark fermentation process. VFA fermentation is optimized by slightly acid pH (6–7), short hydraulic retention time (1–7 days) and high organic load rate (more than 10 gTS L −1 d −1 ). Attention has been focused on VFA exploitation for polyhydroxyalkanoate (PHA) production via a 'feast and famine' strategy performed in sequencing batch reactors. The obtained PHA yields are around 0.4–0.5 gPHA gCOD −1 . Moreover, VFAs allow for the production of biofuels, such as hydrogen and methane, through single‐ or double‐staged anaerobic digestion. Innovative bioelectrochemical upgrade strategies for biogas helps producers to obtain biomethane for the automotive sector. Moreover, biogas has recently been tested for the production of polyhydroxybutyrate, a biodegradable and biocompatible thermoplastic made by microorganisms from C1 carbon sources (CO2 and CH4 ). Digestates from anaerobic bioreactors are still rich in nitrogen and phosphorus compounds. These latter compounds have been identified as critical raw materials due to their low availability in the European Union and to increasing demand from the growing global population. Thus, nutrient recovery from digestate allows users to close the loop of the 'circular economy' approach. © 2019 Society of Chemical Industry